2020
DOI: 10.1111/pedi.13082
|View full text |Cite
|
Sign up to set email alerts
|

Uninterrupted continuous glucose monitoring access is associated with a decrease in HbA1c in youth with type 1 diabetes and public insurance

Abstract: Objective: Continuous glucose monitor (CGM) use is associated with improved glucose control. We describe the effect of continued and interrupted CGM use on hemoglobin A1c (HbA1c) in youth with public insurance. Methods: We reviewed 956 visits from 264 youth with type 1 diabetes (T1D) and public insurance. Demographic data, HbA1c and two-week CGM data were collected. Youth were classified as never user, consistent user, insurance discontinuer, and selfdiscontinuer. Visits were categorized as never-user visit, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 24 publications
4
43
0
Order By: Relevance
“…The only caveat mentioned by some parents was insurance coverage determining their ability to continue using CGM. This finding is consistent with prior research demonstrating that insurance coverage, or lack thereof, determines whether individuals and families are able to sustain CGM use 4,25‐27 . In the United States, individuals from lower socio‐economic groups use CGM at significantly lower rates than those from higher socio‐economic groups; this relationship between socio‐economic status and CGM use is not seen in Germany where insurance and health care delivery differ from the United States 28 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The only caveat mentioned by some parents was insurance coverage determining their ability to continue using CGM. This finding is consistent with prior research demonstrating that insurance coverage, or lack thereof, determines whether individuals and families are able to sustain CGM use 4,25‐27 . In the United States, individuals from lower socio‐economic groups use CGM at significantly lower rates than those from higher socio‐economic groups; this relationship between socio‐economic status and CGM use is not seen in Germany where insurance and health care delivery differ from the United States 28 .…”
Section: Discussionsupporting
confidence: 89%
“…Continuous glucose monitoring (CGM) systems compared with self‐monitoring of blood glucose have resulted in greater improvements in glycaemic outcomes and quality of life in youth with Type 1 diabetes using continuous subcutaneous insulin infusion or multiple daily injection therapy 1,2 . One caveat is that the benefits of CGM correlate with the frequency of and access to ongoing device use 3,4 . Early introduction to CGM in conjunction with health care provider/care team education and insulin‐dosing adjustments can allow for tighter glucose level ranges during the clinical remission phase 5 .…”
Section: Introductionmentioning
confidence: 99%
“…9,10,30,31 The differential use of diabetes technology adoption is considered to be a factor in the inequities seen in HbA1c by SES. 9,32,33 These data call to attention the need for providers to reevaluate their current biases in recommending diabetes technology to youth with T1D. Insurance is inevitably a factor in diabetes technology utilization in the United States, however it should not be one of the most important factors in a provider’s decision to recommend and initiate diabetes technology.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, state Medicaid programs limited access to CGM based on older data showing that youths and young adults had poor adherence to early CGM systems ( 7 ). However, recent randomized controlled trials and real-world studies have shown that publicly insured youths and young adults who are provided access show sustained use of CGM and improved A1C ( 9 , 20 22 ). Data from multistate networks such as the T1DX-QI can advocate for policy changes to allow for universal CGM coverage and decrease the work burden on clinics to increase CGM uptake ( 23 ).…”
Section: Discussionmentioning
confidence: 99%